Social and emotional competence and its association with cyberbullying among adolescents / Thava Viknaraj Sivabalan - Thava Viknaraj, Sivabalan (2021)
Cyberbullying is a growing menace especially in countries like Malaysia which highly focuses on digital industry development. Adolescents are at greater risk since their higher usage of internet mainly on the grounds of social networking. The aim of this study is to describe cyberbullying through various factors and the relationship with social and emotional competence (SEC) using the General Aggression Model as a theoretical framework. The study, conducted through June 2019 to November 2019, adopted a cross sectional study design, among 889 adolescents aged 13 and 14 years old of national secondary schools in Penang, Malaysia. Two-stage random sampling was performed to select schools and study population. Cyberbullying was measured using the European Cyberbullying Intervention Project Questionnaire (ECIPQ) in three distinct domains namely cyber perpetration, cyber victimization and cyber victim-perpetration in the past one month. Cyberbullying prevalence in the past month was 16.6%, 5.8% and 15.0% for cyber victimization, cyber perpetration and cyber victim-perpetration respectively. Infrequent cyberbullying episodes accounted for more than 70.0% of students being at risk to cyberbullying in the past three months. The 14-year-olds were more prone to subject themselves as cyber perpetrators (AOR=2.30, 95%CI 1.09, 4.87). Boys were more likely to be victimized (AOR = 1.90, 95% CI 1.23, 2.95) and at higher risk of becoming online perpetrators themselves (AOR=1.54, 95%CI 1.09, 2.52). With regards to internet use pattern, frequent internet users, those who own an electronic device and those who use the social media and instant messaging apps are more prone to cyberbullying. While having poor mental health was significantly associated with all categories of cyberbullying, cyber victim-perpetrators pose the highest odds of depressive symptoms (AOR=2.15, 95%CI 1.16, 3.99). Traditional bully victim, perpetrator and victim- iv perpetrator were at risk to becoming cyber victims (AOR=3.79, 95%CI 1.93, 7.42), cyber perpetrators (AOR=5.61, 95%CI 1.65, 19.04) and cyber victim-perpetrators (AOR=4.55, 95%CI 1.61, 12.88) respectively. Perceived family support is associated with cyber perpetrators (Mean=4.38 vs 4.13, p<0.001) and victim-perpetrators (Mean=4.38 vs 4.15, p<0.001) while perceived peer support is associated with cyber perpetrators (Mean=4.20 vs 3.99, p<0.05) and victim-perpetrators (Mean=4.20 vs 4.03, p<0.05). Adjusted for all factors, SEC is associated with cybervictimization (AOR=1.04, 95%CI 1.01, 1.06) and cyber victim-perpetration (AOR=0.95, 95%CI 0.93, 0.98). The findings highlight that cyberbullying is a common phenomenon among school-going adolescents of which seven in every ten adolescents reported being at risk to cyberbullying. Factors such as age, gender, ethnicity, internet use pattern, mental health traditional bullying, family and peer support are found to be associated with cyberbullying. High social and emotional competence was found to be a significant protective factor against cyberbullying among adolescents. Skills-based interventions that could increase social and emotional competency of adolescents are important to be considered as possible solutions to reduce cyberbullying. The study findings further recommend cyberbullying to be given equal importance as emphasis to digital development and be addressed through collaborative efforts of various stakeholders such as public health, education, and multimedia agencies. SEC-based interventions must be delivered through universal prevention and whole of organization approaches to ensure effectiveness and sustainability. Keywords: cyberbullying, socio-emotional competence, adolescents, generalized aggression model.